(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the role of historical memory and spiritual heritage in the development of society in Eastern countries. Historical memory is presented as an important factor in understanding national identity, preserving values, and educating future generations in the spirit of patriotism. Based on the rich cultural traditions, religious and spiritual heritage, and historical experience of Eastern peoples, the article highlights memory institutions, mechanisms of shaping historical consciousness, and their impact on socio-spiritual life. In addition, it examines modern methods of preserving historical memory and instilling it in the younger generation, as well as the pedagogical and socio-philosophical aspects of safeguarding national heritage in the context of globalization.